Quadratic Optimal Regulator Design of a Pneumatic Control Valve. (22nd December 2013) - Heidari, Mohammad; Homaei, Hadi
Abstract : Pneumatic control valves are still the most used devices in the process industries, due to their low cost and simplicity. This paper presents a regulator for pneumatic control valves using pole-placement method, optimal control, full-order state observer, and minimum-order state observer and their responses will be compared with each other. Bondgraph method has been used to model the control valve. Simulation results have been made for four models of regulator. The results show that minimum overshoot and settling time are achieved using optimal regulator of pneumatic valve.